Acne vulgaris in adolescence - Büyükgebiz, Atilla; Kınık, Erol (The Turkish Journal of Pediatrics, 1987)
Questionnaires on acne were filled out by 3280 students in the Gülveren district of Ankara. The prevalence of acne in this group was 9.3%. The data from the group of 304 students with acne were analyzed with respect to prevalence, distribution, seasonal change, family history, food habits and type of skin. Of the students with acne, only 10.9% had sought medical attention. It is suggested that the adolescent with acne is not likely to consult a doctor.
Keywords: acne vulgaris; epidemiology